2012
DOI: 10.1016/j.jsat.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, peer, and family influences on smoking among an adolescent psychiatric sample

Abstract: While much is known about adolescent cigarette use and initiation in community samples, less is known about these factors among adolescents in clinic-referred populations or those with severe psychopathology. Data were collected from 106 adolescents aged 12 to 15 years (M = 13.6; SD = .74) recruited from a psychiatric inpatient facility. Hierarchical logistic regressions assessed the relationship between psychological, peer, and family environment factors and smoking at baseline and 18 months post-hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
(102 reference statements)
2
13
0
Order By: Relevance
“…Both young women and Aboriginal young people were significantly more likely to have most or all of their close friends as smokers. Peer group smoking has been shown in other studies to determine whether a young person smokes [20,21], and parental and peer influences were also strong in a study of adolescents with psychiatric problems [22]. This study also found that most minors obtained their tobacco from a shop, suggesting the governance around the sale of tobacco to minors is lax.…”
Section: Discussionsupporting
confidence: 60%
“…Both young women and Aboriginal young people were significantly more likely to have most or all of their close friends as smokers. Peer group smoking has been shown in other studies to determine whether a young person smokes [20,21], and parental and peer influences were also strong in a study of adolescents with psychiatric problems [22]. This study also found that most minors obtained their tobacco from a shop, suggesting the governance around the sale of tobacco to minors is lax.…”
Section: Discussionsupporting
confidence: 60%
“…In addition to these mixed results, several articles found no association between depressive symptoms and tobacco use (Capaldi & Stoolmiller, 1999; Dishion et al, 1999; Pedersen and Von Soest, 2009; Hu, Griesler, Schaffran, & Kandel, 2011; Miller-Johnson et al, 1998; Nargiso et al, 2012; Wu et al, 2008) and no articles reported an association between depressive disorders and nicotine disorders (out of three tests, Dierker et al, 2001; Griesler et al, 2008; Fergusson & Woodward, 2002) when controlling for externalizing symptoms.…”
Section: Resultsmentioning
confidence: 97%
“…Smoking in order to establish friendship was also considered by Naing, Ahmad, Musa, Hamid, Ghazail, and Bakar [ 5 ] to be one of the factors related to smoking habits of male adolescents. Nargiso, Becker, Wolff, Uhl, Simon, Spirito, and Prinstein [ 35 ] also found that friends’ cigarette use had a great effect on smoking outcomes within adolescents. Peer influence was generally the major reason for them taking the habit.…”
Section: Resultsmentioning
confidence: 99%